A look into the practices and challenges of assessing young EFL learners' writing in Croatia. (July 2021) - Patekar, Jakob
Writing in a foreign language is a particularly difficult skill to develop, especially when young learners are concerned because they are parallelly learning to write in their L1 and do not have strong oral foundations in their L2. The issue becomes even more complex when the ways to assess young learners' writing are considered, given that research has shown there is room for improvement regarding English language teachers' assessment literacy. Therefore, the aim of this paper is to examine the practices and challenges of assessing the writing of young EFL learners in Croatia. In the first part of the study, 97 English language teachers working with learners from year 1 to year 4 of elementary school (children aged 7 to 10) took an online questionnaire with close-ended and open-ended questions. In the second part, I analyzed the writing tasks that the learners were assigned by the teachers in the school. The results show that teachers do not always use appropriate writing tasks for summative assessment, that they need more support in creating language tests, and that Croatian universities need to do more to prepare future teachers to teach and assess young English language learners.